"Near misses" in a cataract theatre: how do we improve understanding and documentation?. Issue 12 (18th November 2005) - Mandal, K; Adams, W; Fraser, S
Abstract : Aim: Near miss event reporting is widely used in industry to highlight potentially unsafe areas or practice. The aim of this study was to see if a descriptive method of recording near misses was an appropriate method for use in an ophthalmic operating theatre and to quantify how many untoward events were recorded using this system. Methods: The study was wholly conducted in a cataract theatre in the United Kingdom. The theatre nurse assigned to the patient in their journey through the operating theatre was asked to note any untoward events. As, at present, there is no consensus definition of near misses in ophthalmology the nurses recorded, in free text, any events that they considered to be a deviation from the normal routine in that theatre. Results: Of the 500 cases randomly chosen, 96 "deviations from normal routine" were described in 93 patients—that is, 19% of cases. All forms distributed to the nurses were returned (100% response rate). The commonest abnormal events were intraoperative (69), with a lesser number being recorded preoperatively (27). When these events were further classified, it was thought that 25 could be classified as near misses. One true adverse event was recorded during the study. Conclusions: The results suggest that experienced nursing staff in an ophthalmic theatre are a reliable source for collecting data regarding near misses. A consensus is now required to define near misses in ophthalmology and to devise a user friendly input system that can use these definitions to consistently record these potentially vital events.